A new small molecule inhibitor of soluble guanylate cyclase. Issue 17 (1st September 2015) - Mota, Filipa; Gane, Paul; Hampden-Smith, Kathryn; Allerston, Charles K.; Garthwaite, John; Selwood, David L.
Graphical abstract: Abstract: Soluble guanylate cyclase (sGC) is a haem containing enzyme that regulates cardiovascular homeostasis and multiple mechanisms in the central and peripheral nervous system. Commonly used inhibitors of sGC activity act through oxidation of the haem moiety, however they also bind haemoglobin and this limits their bioavailability for in vivo studies. We have discovered a new class of small molecule inhibitors of sGC and have characterised a compound designatedD12 (compound10 ) which binds to the catalytic domain of the enzyme with a K D of 11 μM in a SPR assay.